Stability and efficiency considerations in the numerical simulation of cone penetration testing in sand. Issue 1 (15th January 2018) - Fan, S.; Bienen, B.; Randolph, M. F.
Abstract : This paper evaluates the effect of analysis parameter choices on the stability and efficiency of modelling cone penetration into sand. This very large deformation quasi-static boundary value problem is modelled here using the Arbitrary Lagrangian-Eulerian (ALE) adaptive mesh technique available within Abaqus/Explicit. The sand response is captured using a hypoplastic constitutive model. It is demonstrated that many choices of analysis parameters lead to spurious results, some of which show clear instability, while other combinations show reasonable stability but over-estimation of the cone resistance. Accuracy of the numerical solution is shown through comparison against centrifuge experimental data for two different relative densities of the sand.